Akad Jual Beli dan Uang Ganti Rugi Rumah Dinas di Kota Langsa Perspektif Fikih Muamalah - Asnita, Dessy; Muttaqin, Zainal; Safitri, Rahmad; Indrayani, Dewi (Lentera: Indonesian Journal of Multidisciplinary Islamic Studies, 2024)
Compensation money handed over by new residents to old residents of official residences in Langsa City as well as handover transactions for official residences have caused problems related to the status of the contract and ownership rights which occurred after payment of a sum of money which was also recognized as compensation money. Through a qualitative approach with descriptive methods, this research aims to determine the status of contracts, compensation money and ownership rights for official residences in Langsa City from a muamalat fiqh perspective. This research reveals that an official residence transaction that is recognized as a sale and purchase agreement is a false sale and purchase agreement because the old occupant as a seller is not the owner of the official residence as al-mabi' so the status of ownership of the official residence does not transfer to the buyer, but remains ownership. National Police. Furthermore, handing over compensation money is not appropriate because it is contrary to the concept of al-ta'widh, causing the transfer of assets from the party giving compensation money to be illegal to own and not permissible to use.